Avaliação da expressão de sistemas de efluxo para resistência antimicrobiana entre amostras clínicas de Pseudomonas aeruginosa - Xavier, Danilo Elias [UNIFESP] (2008)
Multidrug efflux pumps have become increasingly recognized as a major component of resistance among P. aeruginosa. This study investigated the expression level of efflux systems among clinical isolates of P. aeruginosa. Sixty P. aeruginosa isolates were collected from patients with bloodstream infections hospitalized at a Brazilian teaching hospital between July and December 2005. Antimicrobial susceptibility profile was determined by CLSI agar dilution. Genetic relatedness among P. aeruginosa isolates was accessed by PFGE. Transcription levels of four efflux pumps (mexB, mexD, mexF, mexY), oprD and ampC were measured by real time PCR and compared to those of P. aeruginosa ATCC 27853. Detection of acquired metallo-â-lactamases (MâL) was carried out by PCR. Aztreonan (MIC50, 8 ìg/mL; 65% susceptible) exhibited the highest in vitro activity against P. aeruginosa. Only 48.4% of the P. aeruginosa strains were susceptible to imipenem (MIC50, 8 ìg/mL) and meropenem (MIC50, 8 ìg/mL). The MâL genes blaSPM and blaIMP were detected in 23.3% and 1.7% P. aeruginosa isolates, respectively. The overexpression of MexXY-OprM (60%) system was the most frequently detected followed by those of MexAB-OprM (31.7%) and MexCD-OprJ (18.3%) systems. Overexpression of both MexAB-OprM and MexXY-OprM efflux systems was observed in 16.7% of P. aeruginosa isolates. None of the strains overexpressed MexEF-OprN. Hyperexpression of AmpC beta-lactamase was observed in 90% of P. aeruginosa. In contrast, a decrease in the OprD expression was observed in 35% of P. aeruginosa tested and in 50% of the carbapenem-resistant P. aeruginosa isolates. This study shows that the overexpression of efflux systems coupled with AmpC and MâL production effectively contributes to the multi-drug resistant phenotype exhibited by P. aeruginosa clinical strains.